Clinical value of 11C-methionine positron emission tomography in persistent primary hyperparathyroidism—A case report with a mediastinal parathyroid adenoma. (2018) - Møller, M.L.; Rejnmark, L.; Arveschoug, A.K.; Højsgaard, A.; Rolighed, L.
Highlights: Ectopic parathyroid glands should be suspected when positive sestaMIBI uptake is seen in the mediastinum. Other types of imaging (e.g. contrast enhanced CT scan or PET-CT) may confirm the finding of an ectopic parathyroid adenoma. A multidisciplinary effort is necessary to address an intrathoracic adenoma. Abstract: Introduction: Primary hyperparathyroidism (PHPT) is a common endocrine disorder caused by pathologic growth of one or more of the parathyroid glands. Parathyroidectomies (PTX) in patients with PHPT are procedures with low morbidity, few complications, and a high cure rate. However, the parathyroid glands may be found at various anatomical locations and occasionally they are intrathoracic. Case presentation: We present a 57-year-old patient with PHPT. Before the first and second operation, the preoperative imaging indicated pathologic parathyroid tissue in the neck. Due to postoperative persistent hypercalcemia we performed a 11C-methionine positron emission tomography (11C-MET-PET/CT). The scan showed a focus with increased activity in the mediastinum. Due to persistent disease, an ectopic parathyroid gland in the mediastinum was suspected. At a third operation, the parathyroid adenoma was resected through an anterolateral thoracotomy. Biochemical values normalized and bone mineral density improved postoperatively. Hence, an ectopic localization of a parathyroid gland should be considered during the preoperative planning of a PTX, especially in the re-operative setting. A multidisciplinary effort is necessary to address an intrathoracic adenoma. Conclusion: Ectopic parathyroid glands should be suspected when positive sestaMIBI uptake is seen in the mediastinum and other types of imaging (e.g. contrast enhanced CT scan or PET-CT) may confirm the finding of an ectopic parathyroid adenoma. From the present case and previous studies we found 11C-MET-PET/CT valuable in difficult PHPT cases.